Acute mesenteric ischaemia in the elderly - results of combined endovascular and surgical treatment. Primary study - R. Vrba; T. Řezáč; P. Špička; D. Klos; M. Černá; M. Köcher (Scientific Reports)
Abstract Acute mesenteric ischaemia (AMI) is a sudden onset of impaired bowel perfusion. Has a high mortality rate and is difficult to diagnose. Therapy involves endovascular, surgical, or a combination of both. Because of baseline differences, the comparison between endovascular and open surgical treatment is subject to selection bias. The aim of this study was to evaluate the results of treatment of AMI by open or endovascular approach in combination with laparotomy, and evaluation of treatment strategy in similar situations. Clinical data from 21 patients treated for AMI between 2018 and 2022 were retrospectively reviewed and compared. The primary endpoint of the study was in-hospital mortality. The secondary endpoint was the statistical evaluation of risk factors for mortality. All patients underwent acute endovascular revascularisation. Aspiration thromboembolectomy was performed in nine patients, stenting in seven, PTA in one and surgery in three. Endovascular therapy was unsuccessful for technical reasons in 3 patients. None of the monitored parameters reached statistical significance. The best results were achieved in the early diagnosis group. The overall mortality of acute mesenteric ischaemia in our cohort was 34.8%. Acute mesenteric ischaemia is a serious condition affecting mainly elderly patients with a high mortality rate, but the diagnosis of mesenteric ischaemia is not an automatic death sentence. To achieve the best therapeutic outcome, mesenteric ischaemia needs to be diagnosed and treated at an early stage. The best therapeutic outcomes are achieved in centres with 24-hour access to endovascular revascularisation and surgical therapy.